1992
DOI: 10.1038/sc.1992.147
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury: prognosis for ambulation based on quadriceps recovery

Abstract: The purpose of this study was to determine if early recovery of quadricep muscle strength post spinal cord injury (SCI) is a useful predictor of future ambulation. Seventeen C4-T10 motor incomplete (Frankel C) spinal cord injured patients adimitted to our center between March 1988 and April 1990 were examined within 72 hours to one week post injury. All patients had initial quadricep strengths � 2/5 in both legs. Strength in the strongest quadricep was followed prospectively at intervals from admission to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 4 publications
2
42
0
Order By: Relevance
“…Contrary to expectations, the knee extensor strength was not related to ambulatory capacity. Other studies 8,12 have previously reported the knee extensor strength to be associated with ambulatory capacity. Both Crozier et al 8 and Hussey and Stauffer 12 found that a minimum of grade 3 knee extensor strength on the less affected side was required for community ambulation (ie able to walk in-and outdoors).…”
Section: Discussionmentioning
confidence: 88%
“…Contrary to expectations, the knee extensor strength was not related to ambulatory capacity. Other studies 8,12 have previously reported the knee extensor strength to be associated with ambulatory capacity. Both Crozier et al 8 and Hussey and Stauffer 12 found that a minimum of grade 3 knee extensor strength on the less affected side was required for community ambulation (ie able to walk in-and outdoors).…”
Section: Discussionmentioning
confidence: 88%
“…It is considered essential for functional ambulation of traumatic spinal cord injury patients. 23,24 The importance of plantar flexor muscles, however, has been minimized. 25 The role of this muscle group in the gait cycle, being active in weight acceptance (loading response and pre-swing phase), is important to progress and stability.…”
Section: Discussionmentioning
confidence: 99%
“…31 For studying the prognostic value of electrophysiological recordings a gradation of the functional outcome of ambulatory capacity into four functionally relevant categories was applied. 32,33 (a) full ambulatory capacity=no restriction in the activities of daily living and employment due to lower limb de®cit; (b) functional ambulatory capacity=walking daily over a distance of more than 500 m without personal assistance. The use of one or two sticks and/or braces is allowed.…”
Section: Ambulatory Capacitymentioning
confidence: 99%